1973
DOI: 10.1525/aa.1973.75.5.02a00010
|View full text |Cite
|
Sign up to set email alerts
|

The Beginnings of Cultivation in the Midwest‐Riverine Area of the United States

Abstract: Archaeology has become increasingly concerned with the interpretation of prehistoric subsistence settlement systems. In the area of the major river valleys south of the Great Lakes, a significant example of this concern has been the question o f the role of cultivation in changing subsistence economies from the Late Archaic through Woodland periods. This article assembles all published (and unpublished) archaeological information on the remains o f cultivated plants recovered f r o m Woodland sites in the Midw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Two accelerator mass spectrometry (AMS) Crites 1987;Smith 1992), and at the Scioto tradition Hopewell Harness Mound (Ford 1987). Despite theoretical assumptions about the early presence of maize in major river valleys in the Americas (Lathrap 1987;Struever and Vickery 1973), maize has until now not been established in the Mississippi River valley during Middle Woodland times.…”
mentioning
confidence: 99%
“…Two accelerator mass spectrometry (AMS) Crites 1987;Smith 1992), and at the Scioto tradition Hopewell Harness Mound (Ford 1987). Despite theoretical assumptions about the early presence of maize in major river valleys in the Americas (Lathrap 1987;Struever and Vickery 1973), maize has until now not been established in the Mississippi River valley during Middle Woodland times.…”
mentioning
confidence: 99%
“…As noted above, tropical domesticates had reached the East prior to 2000 B.C., and there is good evidence of cultivation of native seed plants in the Kentucky and Ohio area by 1000 B.C. (Struever and Vickery 1973). Ceramics probably 21 appeared somewhat earlier than this in the third millennium B.C.…”
Section: Pointmentioning
confidence: 87%
“…600 was a product of a shift toward unfavourable climate. Subsequent research, reported by Streuver and Vickery, added the details to Griffin's surmise (Streuver and Vickery 1973). Finally, Baerreis, Bryson and Kutzbach (1976) placed the sequence of events in a firm palaeoclimatic perspective.…”
Section: Culture and Civilization In North Americamentioning
confidence: 98%